Numerical simulation of dense fluid-particle flows using computational fluid dynamics (CFD) and discrete element method (DEM) - Iqbal, Naveed; Rauh, Cornelia; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2012)
Discrete Element Method (DEM) has been successfully coupled with Computational Fluid Dynamics (CFD) in the framework of OpenFOAM an open source CFD simulation code. In the current study, at first the model is validated with the simple test case of spherical particle comparing the results with the analytical solution. Then the simulation of a gaseous fluidized bed is considered. The coupled mass and momentum balance equations are used to calculate the flow behavior, particle fluidization and bubble formation. The dimensions of the simulation domain are similar to Link et al. (2005) but with different stiffness of particles. The higher velocity of gaseous fluid relative to particles entering through a jet causes the particles to fluidize. The particles behavior, fluidization, bubble formation and the velocity vectors of particles show a good agreement with the literature.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.numeri_1